2022
DOI: 10.1371/journal.pone.0274305
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between physical activity and musculoskeletal disorders among low income housewives in Kuala Lumpur: A cross sectional study

Abstract: Housewives play a crucial role in their families’ and communities’ quality of life. However, musculoskeletal disorders are common among housewives due to housework and lack of physical activity. These musculoskeletal problems have been associated to leisure physical activity. As a result, the goal of this study was to determine the incidence of musculoskeletal problems and their association to physical activity among low-income women in Kuala Lumpur. A cross-sectional research was done among 82 housewives in K… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
4
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 37 publications
1
4
0
1
Order By: Relevance
“…The present study nds negligible associations for neck pain and some other body regions indicate that factors other than employment status and age may be more in uential in determining pain prevalence such as quality of life [18], low socio economic status [19], poor posture and diet [20]. These results were supported by study conducted by Saat et al [21]. Employers regard to their age may need to tailor their health and safety policies to address their speci c needs, like ergonomic accommodations for older workers or implementing age-appropriate practice setting and specialty area [22].…”
Section: Discussionsupporting
confidence: 84%
“…The present study nds negligible associations for neck pain and some other body regions indicate that factors other than employment status and age may be more in uential in determining pain prevalence such as quality of life [18], low socio economic status [19], poor posture and diet [20]. These results were supported by study conducted by Saat et al [21]. Employers regard to their age may need to tailor their health and safety policies to address their speci c needs, like ergonomic accommodations for older workers or implementing age-appropriate practice setting and specialty area [22].…”
Section: Discussionsupporting
confidence: 84%
“…Housewives frequently struggle to find time for physical exercise amidst their household responsibilities. Research has consistently demonstrated that housewives exhibit lower levels of PA [ 5 ]. This trend is not unique to any specific region; in Iran, for example, studies have similarly revealed that PA among housewives is markedly low [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Overweight/obesity is recognized as major risk factor for multiple non-communicable diseases (NCDs) such as type 2 diabetes, certain types of cancers, musculoskeletal disorders and cardiovascular diseases [ 6 8 ]. In 2019, around 5 million deaths from NCDs were linked to having a higher than recommended body mass index (BMI) [ 9 ].…”
Section: Introductionmentioning
confidence: 99%